2015
DOI: 10.1162/pres_a_00229
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing and Immersive Visualization for Improved Perception of Ancient Artifacts

Abstract: This article investigates the use of 3D immersive virtual environments and 3D prints for interaction with past material culture over traditional observation without manipulation. Our work is motivated by studies in heritage, museum, and cognitive sciences indicating the importance of object manipulation for understanding present and ancient artifacts. While virtual immersive environments and 3D prints have started to be incorporated in heritage research and museum displays as a way to provide improved manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 39 publications
1
46
0
2
Order By: Relevance
“…Di Franco et al. () presented a study on how museum visitors regard authenticity of objects, finding that it does not play a particularly prominent role for some visitors, but was not completely unimportant. They found that authenticity takes a backseat to the opportunity to gain knowledge, constituting a contrast to the feedback of visitors from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Franco et al. () presented a study on how museum visitors regard authenticity of objects, finding that it does not play a particularly prominent role for some visitors, but was not completely unimportant. They found that authenticity takes a backseat to the opportunity to gain knowledge, constituting a contrast to the feedback of visitors from this study.…”
Section: Discussionmentioning
confidence: 99%
“…) although the number of studies that evaluate this latter approach is limited (Di Franco et al. ; Neumüller et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the survey will be compared with other similar exercises where different other multimodal approaches were also involved. 48 This research has elucidated how 3-D scanning, virtual anastylosis, and web sharing can contribute to the improvement of museum policies in the field of public outreach, showing how a case of limited accessibility, represented by the state of a Greek statue irremediably divided in pieces between two museums, can become the public's path to virtual discovery of a new masterpiece of Greek sculpture.…”
Section: Sd D U a Samentioning
confidence: 98%
“…Archaeologists in particular have found 3D scanning useful for producing realistic historical reconstructions of objects and places (Grosman ; Di Franco et al. ; Forte ). Across many disciplines, much of this work has focused on what might be referred to as the “affordances” of digital fabrication technologies for learning environments (Norman ), where the specific qualities and context‐specific permutations of these technologies might enable the re‐creation of objects in 3D or the visualization of multiple layered settings.…”
Section: Setting the Stage: Digital Fabrication In Museumsmentioning
confidence: 99%